Intensitas Pemberitaan Injil Berdasarkan Kajian Teologis 1 Korintus 9:19-23 Di Tengah-Tengah Zaman Digital - Ayub Rusmanto; Wahyu Lasut; Slamet Jariyanto (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2022)
This paper analyzes the intensity of the relevant gospel preaching based on the theological study of 1 Corinthians 9:19-23 in the midst of the digital age. There are several substances in the study of 1 Corinthians 9:19-23 that have been studied by several previous researchers, but they investigate from different sides. Thus, this paper focuses on the intensity of relevant gospel preaching in the midst of the digital age, seriousness and seriousness are needed in carrying it out. The method used in this study uses a qualitative method with a literature study approach and uses a bible hermeneutics approach. In order to find the results of the intensity of relevant gospel preaching based on the theological study of 1 Corinthians 9:19-23 in the midst of the digital age, the author finds that the church in preaching the gospel needs to improve, understand and open up to the progress of media development in the midst of the digital age, because the media is an effective means of reaching souls in today's digital age. Thus, the author concludes that the intensity of relevant gospel preaching based on the theological study of 1 Corinthians 9:19-23 in the midst of the digital age can be done through live streaming preaching, video recordings, audio recordings, zoom, google meet, and steps for preaching the gospel. which continues to be updated status via Facebook and Instagram. Because the preaching of the gospel through the media is very effective and relevant in the midst of today's digital age.